Philadelphia chromosome-positive acute lymphoblastic leukemia in childhood - Hong Hoe Koo (Korean Pediatric Society, 2011)
In pediatric patients with acute lymphoblastic leukemia (ALL), the Philadelphia chromosome translocation is uncommon, with a frequency of less than 5%. However, it is classified as a high or very high risk, and only 20-30% of Philadelphia chromosome-positive (Ph+) children with ALL are cured with chemotherapy alone. Allogeneic hematopoietic stem cell transplantation from a closely matched donor cures 60% of patients in first complete remission. Recent data suggest that chemotherapy plus tyrosine kinase inhibitors (TKIs) may be the initial treatment of choice for Ph+ ALL in children. However, longer observation is required to determine whether long-term outcome with intensive imatinib and chemotherapy is indeed equivalent to that with allogeneic related or alternative donor hematopoietic stem cell transplantation (HSCT). Reports on the use of second-generation TKIs in children with Ph+ ALL are limited. A few case reports have indicated the feasibility and clinical benefit of using dasatinib as salvage therapy enabling HSCT. However, more extensive data from clinical trials are needed to determine whether the administration of second-generation TKIs in children is comparable to that in adults. Because Ph+ ALL is rare in children, the question of whether HSCT could be a dispensable part of their therapy may not be answered for some time. An international multicenter study is needed to answer the question of whether imatinib plus chemotherapy could replace sibling allogeneic HSCT in children with Ph+ ALL.